2017
DOI: 10.4172/2161-0940.1000254
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Utilization of Long Acting and Permanent Contraceptive Methods among Women of Reproductive Age Group in Jigjiga Town

Abstract: Background: Contraceptive use including short acting, long acting and permanent methods positively influence the socio-economic development of a nation by allowing families to space and limit their family size to their economic capacity. Demand for Long acting and permanent methods (LAPM) of contraception as determined by utilization and unmet need for LAPMs provide reliable information for providers.Objective: To assess factors associated with utilization level of long acting contraceptive methods and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…However, our results do not match with studies conducted in Ethiopia and Iran [31,32]. Other studies conducted in various countries found that age was not significantly associated with the use of LARC[3,8,23,24,33]. This study provides the evidence that, in Nepal, women’s age is one of the contributing factors of LARC use.…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results do not match with studies conducted in Ethiopia and Iran [31,32]. Other studies conducted in various countries found that age was not significantly associated with the use of LARC[3,8,23,24,33]. This study provides the evidence that, in Nepal, women’s age is one of the contributing factors of LARC use.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is higher than the 2016 EDHS data (11.6%), 17 Janamora District (12.9%), 15 Jinka town (7.3%), 32 and Jijiga town (8.8%). 21 The result was also higher than a study in Uganda (7.7%) in urban and (10.9%) in rural women. 40 But this is lower than studies from Gondar town (34.7%), 14 Debre Markos town (19.5%), 16 Mekelle town (19.9%) in urban and (37.8%) in a rural setting, 22 Nekemte town (20%), 19 and Bombe District, Southern Ethiopia (16.3%).…”
Section: Discussionmentioning
confidence: 56%
“…For instance, religious, marital status, and residence differences may affect LACM utilization. Lower LACM prevalence by studies from Jinka and Jijiga town 21,32 might be due to these socio-cultural differences.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, merchants by occupation more likely to utilized LTFP methods than their counter parts. Occupation of the women was associated to FP utilization in different studies conducted in Ethiopia [15, 2527]. Monthly income of the household was positively associated with LTFP utilization.…”
Section: Discussionmentioning
confidence: 99%